PENGARUH KERAGAMAN PRODUK DAN LOKASI TERHADAP MINAT BELI KONSUMEN PADA RUMAH MAKAN ARUM MLANDINGAN SITUBONDO DENGAN KEPERCAYAAN KONSUMEN SEBAGAI VARIABEL INTERVENING - Saputra, Andre Agung; Hamdun, Edy Kusnadi; Praja, Yudha (Fakultas Ekonomi dan Bisnis, 2023)
Marketing management can be interpreted as an analysis of planning, implementing and controlling programs designed to create, build and maintain favorable exchange rates with target markets with a view to achieving the goals set by the organization at the request of management. The purpose of this study was to analyze and test the effect of product diversity and location on consumer buying interest at Arum Mlandingan Situbondo Restaurant with consumer trust as an intervening variable. The sampling technique was determined by the Simple random sampling method. Data analysis and hypothesis testing in this study used the Structural-Partial Least Square Equation Model (PLS-SEM). The results of the direct effect hypothesis test using the Smart PLS 3.0 application, indicate that product diversity has a significant effect on consumer buying interest. Location has a significant effect on consumer buying interest. Product diversity has a significant effect on consumer confidence. Location has a positive but not significant effect on consumer confidence. Product diversity has a significant effect on consumer buying interest through consumer trust. Location influences Consumer Purchase Interest through Consumer Trust.